ادریس قمر کے کلام کا علامتی و استعاراتی نظام:ایک تنقیدی مطالعہ: The Symbolic and Metaphorical System in the Poetry of Idrees Qamar: A Study (Al-Aasar, 2026)
Idrees Qamar occupied a unique and respected place in the literary landscape of Chichawatni. His poetry was deeply rooted in truthfulness and genuine emotional experience. Beyond the theme of love, he gave a powerful voice to the marginalized, the poor, and the working class, portraying their hardship and social injustices with sensitivity and insight. By critically addressing the rulers and the privileged elite of his era, he courageously unveiled elite of realities of oppression and exploitation. Rich in symbols and metaphors, the poetry of Idrees Qamer stands as a testament to his intellectual depth, artistic vision, and creative consciousness.